Model Dinamik Manajemen Usahatani Ubikayu - Ariadi, Bambang Yudi; K, Maman Haeruman; Rochdiani, Dini; Rasmikayati, Elly (Program Studi Agribisnis, Fakultas Pertanian, Universitas Muhammadiyah Yogyakarta, 2015)
Cassava production is very important in Kabupaten Trenggalek to fulfill need of local industries and market demand from outside region. In fact, cassava produc-tion is not stable, one of the cause is price fluctuation. Before planting time, cassava price is expencive and farmers are interested to plant, however, at harvest time the price is fall so that farmers get lose. Such condition caused farmers to change to plant others commodity. The study aimed to: 1) conduct maping of the real system of cassava farm manage-ment and farmers performance in Kabupaten Trenggalek East Java; 2) analyze the components and its relevant on cassava farm management and farmers performance; 3) design model of cassava farm management and farmersÂ performance in the perspective of system dynamic. The system dynamic analysis that did maping the real system creat a mental model, causal loop diagram (CLD). There are two model sub-systems, they are sub-system of farm management are sub-system of farmers performance. Based on the mental model, next we design Flow Diagram (FD) of the model and model validation by using software of Vensim. In the model of farm management and farmers performance, it was found a leverage factor namely technology of integrated farming system (IFS). If a component of IFS is change or slightly increased/decreased, the whole system will also changed.